2013
DOI: 10.1002/mbo3.65
|View full text |Cite
|
Sign up to set email alerts
|

The anguibactin biosynthesis and transport genes are encoded in the chromosome of Vibrio harveyi: a possible evolutionary origin for the pJM1 plasmid–encoded system of Vibrio anguillarum?

Abstract: Many Vibrio anguillarum serotype O1 strains carry 65-kb pJM1-type plasmids harboring genes involved in siderophore anguibactin biosynthesis and transport. The anguibactin system is an essential factor for V. anguillarum to survive under iron-limiting conditions, and as a consequence, it is a very important virulence factor of this bacterium. Our comparative analysis of genomic data identified a cluster harboring homologs of anguibactin biosynthesis and transport genes in the chromosome of Vibrio harveyi. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…These two sequenced V. harveyi strains, BAA-1116 and HY01, have been proposed to be classified as V. campbellii by microarray-based comparative genomic hybridization (CGH) and multilocus sequence analyses (MLSA) (Lin et al 2010). We also demonstrated that V. campbellii but not V. harveyi , as classified by CGH and MLSA, produces anguibactin by specific bioassay (Naka et al 2013b). Furthermore, it was also reported that V. campbellii DS40M4 produces anguibactin, and the anguibactin cluster was found in its draft genome sequence (Dias et al 2012; Sandy et al 2010).…”
Section: Chromosome-encoded Anguibactin System In V Harveyimentioning
confidence: 74%
See 1 more Smart Citation
“…These two sequenced V. harveyi strains, BAA-1116 and HY01, have been proposed to be classified as V. campbellii by microarray-based comparative genomic hybridization (CGH) and multilocus sequence analyses (MLSA) (Lin et al 2010). We also demonstrated that V. campbellii but not V. harveyi , as classified by CGH and MLSA, produces anguibactin by specific bioassay (Naka et al 2013b). Furthermore, it was also reported that V. campbellii DS40M4 produces anguibactin, and the anguibactin cluster was found in its draft genome sequence (Dias et al 2012; Sandy et al 2010).…”
Section: Chromosome-encoded Anguibactin System In V Harveyimentioning
confidence: 74%
“…V. harveyi is a marine bacterium as well, and some of the strains are pathogens that mainly affect the shrimp aquaculture industry. Two sequenced strains of V. harveyi , BAA-1116 and HY01, carry a gene cluster containing homologues of the majority of anguibactin biosynthesis and transport genes found in the pJM1 plasmid of V. anguillarum (Naka et al 2013b) (Fig. 4).…”
Section: Chromosome-encoded Anguibactin System In V Harveyimentioning
confidence: 99%
“…This suggests that V. anguillarum acquired the anguibactin iron transport system by horizontal transmission. Homologs of the plasmid genes are present in the chromosome of Vibrio harveyi, which also produces anguibactin, further supporting horizontal transfer of the genes (67).…”
Section: Transport Of Iron Complexesmentioning
confidence: 82%
“…A more striking discovery was the identification of an angR gene homolog in a whole-genome sequence of Vibrio harveyi (211). Further detailed analysis revealed that the chromosome of this bacterium encodes the complete ITB operon including the upstream angM gene and downstream genes angH, angU, and angN.…”
Section: Heterogeneity Of the Pjm1 Determinantsmentioning
confidence: 99%
“…Further detailed analysis revealed that the chromosome of this bacterium encodes the complete ITB operon including the upstream angM gene and downstream genes angH, angU, and angN. In the case of V. harveyi the angBG gene is located in proximity to the cluster, while on the pJM1 plasmids the two clusters are located in noncontiguous regions (211).…”
Section: Heterogeneity Of the Pjm1 Determinantsmentioning
confidence: 99%